Respostas
respondido por:
44
4x^2-12x+5=0
delta=b^2-4ac
delta=(-12)^2-4.4.5
delta=144-80
delta=64
x=-b-/+ raiz de delta/2a
x=-(-12)-8/2.4
x=12-8/8
x=4/8 (:4)
x=1/2
x=-(-12)+8/2.4
x=12+8/8
x=20/8 (:4)
x=5/2
delta=b^2-4ac
delta=(-12)^2-4.4.5
delta=144-80
delta=64
x=-b-/+ raiz de delta/2a
x=-(-12)-8/2.4
x=12-8/8
x=4/8 (:4)
x=1/2
x=-(-12)+8/2.4
x=12+8/8
x=20/8 (:4)
x=5/2
respondido por:
55
Primeiro colocamos os valores de a,b.c em evidência:
4x² -12x+5 =0
a:4 Δ=b²-4ac
b:-12 Δ=(-12)²-4. 4.5
c:5 Δ=144 -80
Δ=64
Formula de Bhaskara:
x= -b+-√Δ
2a
x= -(-12)+-√64
2.4
x= +12+-8
8
x'= 12-8= 4 =0,5
8 8
x"=12+8 = 20 = 2,5
8 8
4x² -12x+5 =0
a:4 Δ=b²-4ac
b:-12 Δ=(-12)²-4. 4.5
c:5 Δ=144 -80
Δ=64
Formula de Bhaskara:
x= -b+-√Δ
2a
x= -(-12)+-√64
2.4
x= +12+-8
8
x'= 12-8= 4 =0,5
8 8
x"=12+8 = 20 = 2,5
8 8
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás